Strengthen Interpersonal Communication in Improving Library Services for People with Disabilities - Muhamad Bisri Mustofa; Muhamad Khadavi Febrian; Siti Wuryan (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2023)
This study aims to strengthen interpersonal communication in improving library services for people with disabilities. This research is motivated by the neglect of people with disabilities when communicating their needs in library services. The method used in this study is a qualitative method, by conducting an in-depth case study approach. Data was obtained through online observation from websites that support data retrieval, in the form of books or journals available. The results showed that the training of librarians in interpersonal communication with users with disabilities should be implemented, librarians must be able to adapt to information and Communication Technology. Communicate interpersonally librarians must also pay attention to five important points, namely (1) Reliability, (2) Responsiveness, (3) Assurance, (4) Emphaty, (5) Tangible. Based on these results, interpersonal communication plays a role in improving library services for people with disabilities. The important role of interpersonal communication is because librarians can understand and help people with disabilities, and provide the same feelings that others get. And can minimize misunderstandings that will occur between librarians and users with disabilities.